Fake goods - Susan Zieger (Finance and Society, 2023)
The early 2020s commonplace that everything seems unreal is a material truth. Advances in logistics are generating more counterfeits. Blockchain technology promises to help stem the deluge of counterfeit products, but the Blockchain dream also reminds us that logistics is an imperfect performative art. The material good becomes the unreal figure, while airy speculation assumes greater predictability. All that is solid melts into air, but all that is air comes back to the ground.
Keywords: 300; blockchain; conterfeit goods; crypto; Logistics; NFTs; supply chains